“Desarrollo del sistema de seguimiento a graduados para la Dirección Académica de la Universidad Técnica de Cotopaxi” - Coyago Pacheco, Miguel Angel (2024)
The General Academic Direction of the Technical University of Cotopaxi identified the need to manage the graduate follow-up process to obtain valuable information on the professional performance of its graduates. With the overall objective of designing and implementing a graduate follow-up system that facilitates data-based decision making, it developed a digital platform to centralize, organize and visualize the surveys applied to graduates. It used a methodology that included requirements analysis, database creation and user interface design. Multiple relational tables were structured to reflect the hierarchy and relationships between surveys, answers, careers, faculties, and others. As a result, it obtained oda functional system that allows users to enter, consult and analyze surveys and their effective responses, providing a clear view of the status and progress of the university's graduates. This tool has proven to be essential for the management in its mission to ensure the success of the university's graduates.